Unmasked religion as a given of religion in the secularized everyday-life - Gutauskas, Mintautas (Religija ir kultūra, 2008)
The article raises the hypothesis that religion is not an internal feature of the secularized everyday-life, but religion is given in its undisguised semblance. The character of unmasking of religion in the secularized everyday-life is explained with reference to J. Baudrillard’s interpretation of simulation and simulacra and to P. Sloterdijk’s analysis of cynical consciousness. The object of the article is the ontological presuppositions of such unmaskings. It is supposed that the presupposition of all unmaskings of religion is the tumbling acceptance of God’s absolute reality. The atheistic denial of God is analyzed as a form of unmasking. Further the unmasking of religion as simulacra is examined. It discloses religion as a spectacle, which masks true dimension of reality – power, mental reality or economical dimension. According to this various forms of unmasking are distinguished. The character of unmasking thinking is explained with the reference to H. G. Gadamer’s concept of pre-text ant to P. Sloterdijk’s interpretation of the cynical truth as naked truth. It is revealed how the unmasking thought learns to find the pre-text behind every text, the naked truth behind every truth. Finally raises the question about the limits of unmaskings and the possibility of religion in the periphery of these unmaskings.